Modelling cognitive deficits in Parkinson's disease: Is CA2 a gateway for hippocampal synucleinopathy? - Cinar, Elif; Yalcin-Cakmakli, Gul; Saka, Esen; Ulusoy, Ayse; Yuruker, Sinan; Elibol, Bulent; Tel, Banu C. (Experimental neurology, 2020)
Cognitive dysfunction is one of the most disabling non-motor symptoms of Parkinson's disease (PD), though its pathological correlates still remain elusive. Hippocampal Lewy pathology has recently been correlated by compelling evidence from post-mortem and imaging studies. Animal models recapitulating cognitive impairment in PD are essential to better understand the underlying pathophysiology. To investigate the hippocampal involvement in cognitive dysfunction of PD, we generated an experimental model by inducing midbrain and hippocampal α-synuclein pathology simultaneously. Rats were injected either with human α-synuclein or green fluorescent protein (GFP) expressing adeno-associated viral vectors (AAV), or saline bilaterally into substantia nigra (SN) and dentate gyrus (DG). A group of untreated animals were used as naïve controls. Cognitive and behavioral changes were evaluated with tests probing for spatial learning, short-term memory, anxiety and hedonistic behavior. Immunohistochemical staining, immunoblotting and stereological analysis were performed for pathological characterization. Bilateral α-synuclein overexpression in SN and DG led to mild but significant motor impairment as well as dysfunctions in short-term memory and spatial learning. There was no hedonistic deficit, whereas a hypo-anxious state was induced. While stereological analysis revealed no significant neuronal loss in any sectors of cornu ammonis, there was considerable decrease (43%) in TH+-neurons in SN pars compacta supporting the well-known vulnerability of nigral dopaminergic neurons to α-synuclein mediated neurodegeneration. On the other hand, synaptophysin levels decreased in similar amounts both in striatum and hippocampus, suggesting comparable synaptic loss in target areas. Interestingly, phosphorylated-S129-α-synuclein staining revealed significant expression in CA2 characterized by more mature and dense cellular accumulations compared to CA1-CA3 sub-regions displaying more diffuse grain-like aggregates, suggesting preferential susceptibility of CA2 to produce α-synuclein induced pathology. Bilateral α-synuclein overexpression in DG and SN reproduced partial motor and hippocampus related cognitive deficits. Using this model, we showed a predisposition of CA2 for pathological α-synuclein accumulation, which may provide further insights for future experimental and clinical studies. •rAAV5-h-α-synuclein injected bilaterally both into substantia nigra and dentate gyrus.•α-Synuclein overexpressing animals showed mild but significant motor and cognitive impairments.•α-Synuclein overexpression lead to TH+-neuronal loss in SN with decreased synaptophysin levels in striatum.•Despite no significant neuronal loss in hippocampus, decreased synaptophysin levels suggested synaptic degeneration.•Among hippocampal subregions CA2 was the most affected area with dense p-(Ser129)-α-synuclein accumulation.